The benefit of hippotherapy for improvement of attention and memory in children with cerebral palsy: A pilot study - Eva Krejčí; Miroslav Janura; Zdeněk Svoboda (Palacký University Olomouc, 2015)
Background: The research is based on an assumption that the hypokinesia induced by cerebral palsy (CP) leads to inhibition of some mental functions. The method we used to treat patients with CP, hippotherapy (HT), is a treatment using horses and belongs to proprioceptive-neuromuscular-facilitative methods. Objective: The aim of the research was to determine the benefit of HT on attention and memory of patients with CP. Methods: There were two groups of patients: short-term HT (n = 11; 8 females and 3 males, age 15.4 ± 5.3 years) and long-term HT (n = 9; 7 females and 2 males, age 10.8 ± 2.7 years). The short-term HT group participated in daily 30 minute-long HT sessions for duration of a week-long summer therapy camp; while with the long-term HT group, HT sessions of the same length were used weekly for 5-6 weeks. Attention and memory skills were assessed with "Numeric square test" and "Verbal learning test", respectively. Both tests were undertaken before starting and after concluding the camp or the 5-6 week long HT period. Results: Attention improvement demonstrated in a significant decrease of an average time of "Numeric square test". The improvement was seen in both long-term HT (15.7 seconds overall average time reduction after HT, p < .01) and short-term HT (20.8 seconds reduction, p < .01) groups. Short-term memory improvement was found in the long-term HT group, demonstrated by a higher number of memorized words (more than half of the patients memorized on average 10.5 more words after HT) (p < .05). While the short-term HT group did not show significant improvement of attention or short-term memory, the average number of memorized words after a diversion of attention and a 30 minute delay increased by 4.1, showing an improvement (p < .05) of long-term memory. Conclusions: Our results suggest that hippotherapy as a part of comprehensive therapy in patients with CP leads to improvement of memory and attention skill.